Examining the Prevalence and Types of Alcohol and Drug Use among Kaimosi Friends University Students - Okanga, Anne (African Journal of Education and Practice, 2025)
Purpose: This study examined the prevalence, types, and patterns of alcohol and drug use among students at Kaimosi Friends University (KAFU), as well as their awareness and knowledge of substance abuse. Methodology: A descriptive cross-sectional research design was employed, with a stratified random sample of 350 students selected from a population of 4,800. Data collection was done using structured questionnaires adapted from NACADA in April 2025, and the analysis involved descriptive statistics using SPSS. Ethical clearance was granted by MMUST, with participant confidentiality and voluntary participation ensured. Findings: Findings revealed that 65.1% of respondents were male, with an average age of 21.8 years. Most were government-sponsored (76%), and the largest proportion (68%) came from the School of Education and Social Sciences. A majority (57%) lived off-campus, mainly in Cheptulu (28%) and Jivuye (16%). Lifetime substance use stood at 70%, and 60% had used substances in the past year. Alcohol was the most commonly used substance (70%), followed by cigarettes (50%) and marijuana (40%). Other substances like codeine, prescription drugs, shisha, miraa, and vape products had usage rates between 20–30%, while fewer than 10% reported using hard drugs such as heroin and cocaine. Most students began using substances between the ages of 15–19, with accessibility playing a significant role especially for alcohol, cigarettes, and miraa. Unique Contribution to Theory, Practice and Policy: The study provides insight into prevalence and types of substances abused as well as recommending measures to inform policy in regulating access to substances of abuse as well as improving on campus support services.